Production of high quality syngas from argon/water plasma gasification of biomass and waste - Hlina, M; Hrabovsky, M; Kavka, T; Konrad, M (Waste management (New York, N.Y.), 2014)
Extremely hot thermal plasma was used for the gasification of biomass (spruce sawdust, wood pellets) and waste (waste plastics, pyrolysis oil). The plasma was produced by a plasma torch with DC electric arc using unique hybrid stabilization. The torch input power of 100-110 kW and the mass flow rate of the gasified materials of tens kg/h was set up during experiments. Produced synthetic gas featured very high content of hydrogen and carbon monoxide (together approximately 90%) that is in a good agreement with theory. High quality of the produced gas is given by extreme parameters of used plasma--composition, very high temperature and low mass flow rate.
Keywords: Gases; biomasa; biopaliva; tuhý odpad; Biomass; plastické hmoty; Carbon Monoxide; Biofuels; plyny; Tar; Wood; design vybavení; odpadky - odstraňování; Hydrogen; Plasma; Plastics; dřevo; Equipment Design; Gasification; oxid uhelnatý; vodík; Solid Waste; Refuse Disposal